"When the surgery was over, I felt like the worst part had passed": experiences of parents of children with craniosynostosis. Issue 2 (9th March 2022) - Zerpe, Anna S.; Nowinski, Daniel; Ramklint, Mia; Öster, Caisa
Abstract: Purpose: Parents of children scheduled for surgery often experience emotional distress and anxiety. This study aimed to explore parents' experiences of hospital care after their child's craniosynostosis surgery and their perception of support during the year after discharge. Design and Methods: A purposive sample of 19 parents of 12 children with nonsyndromic craniosynostosis, who had undergone surgery, was recruited from one of two national centers in Sweden. An interview was conducted 1 year after the child's surgery, from September 2017 to August 2018. The interviews followed a semistructured interview guide, were recorded, transcribed verbatim, and analyzed using inductive content analysis. Results: The analysis yielded six categories with subcategories as follows: (1) cared for and confident: the hospital staff was perceived as kind, professional, and reliable. (2) Alone and abandoned: sometimes, parents found it hard to initiate contact with professionals during hospitalization and after discharge. (3) The importance of information: thorough information was perceived as essential and the need for information varied during postsurgery period. (4) Feelings of worry: some parents remained worried about risks during recovery and were concerned about comorbidities and development. (5) Alright after all: parents felt that the worst part had been before surgery. (6) The need for support: parents were generally satisfied with the support offered and they often received support from family and friends, or other parents through social media/online forums. Practice Implications: Healthcare professionals must be responsive to what support parents need at different stages in the care process and be aware that parents sometimes hesitate to initiate contact and ask for help and support. Support from healthcare professionals to everyone in the follow‐up program, as a default, might be more accessible or acceptable for some parents. Providing online support from professionals should be considered and caregivers could also facilitate peer support among parents, either face‐to‐face or online.